PEMANFAATAN RUANG KELUARGA DI PERUMAHAN VILLA GARDENIA PEKANBARU - ", Surianto; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The family room is a space that is very important. Many reasons that make the familyroom is an important one because in this space the center of family interaction takes place.Family interaction can be done in a variety of daily routine, when to eat, when do the daily workand so on. According to Abu Ahmadi and Supriono Widodo Social interaction is the key to allsocial life is therefore without any social interaction there can be no life together. Socialinteraction is intended as a reciprocal influence between individuals with groups in their effortsto solve problems that are expected and in their efforts to achieve their goals. Place into aresearch location is in Housing Villa Gardenia in the Banyan, Water Black RT 15 RW 5 Labuhvillages New District of Umbrella Sekaki Pekanbaru. The population in this study was 83homeowners diperumahan Villa Gardenia, with a sampling technique in this research is to usethe census method. The method used in this paper is a quantitative descriptive. which in thisstudy the author describes the data obtained in the form of tables and described in the discussionof the sentence into problems examined it aims to facilitate understanding of the content of thisresearch. From these results it can be concluded that each family member has a function roomthat family is different also.Keywords: Utilization, Family Room, Residential.